Rancang Bangun Aplikasi Computer-based Test (CBT) serta Optimasinya Menggunakan Cache dan Queue Job - Rahmat Siswanto; Dwi Senjaya A. Morang (Jurnal Komputer Terapan, 2022)
Examinations in schools that still use paper require a great deal of time, effort and money to implement, especially in the activities of printing, duplicating and distributing exam questions to students who will take the exam. Therefore, we need a system that can facilitate the filling, duplication and distribution of questions at a small cost. Based on these problems, a web-based CBT application was built that can be accessed anywhere and anytime and can work on multiple platforms (multi-platform). This system was built using the prototyping method to make it easier for developers and users to develop applications from the initial prototype to the production stage. In practice, this application is expected to be able to accommodate exam activities for all students in the school at the same time. Based on this, the application that is made must have reliability and accuracy starting from the process of carrying out the exam to displaying the results. Researchers apply a cache and queue job system to the application to get maximum results. From the results of tests that have been carried out in three stages, the results show that this web-based CBT application is able to accommodate exam activities in schools with a total of 250 students in one exam session and can display a recap of exam results from all participants.